USPs and non-coding RNAs: Unraveling their interplay within tumor microenvironment for targeted cancer therapy - Yongqing Xu; Jin Wang; Xin Deng; Hongli Gao; Fei Xing; Hao Ding; Lianyue Qu; Zhuo Xi (Pharmacological Research)
Cancer represents a significant global health threat, with the World Health Organization reporting millions of new cases annually. Dysregulation in cellular homestasis leads to the aggressive and heterogeneous nature of cancers. Conventional treatments encounter challenges due to the inhomogeneity of tumor microenvironment (TME). Ubiquitination and deubiquitination, as typical post-transcriptional modifications (PTMs), play crucial roles in various cellular processes, with deubiquitinating enzymes (DUBs) influencing cancer progression. Over 100 DUB species, particularly the major ubiquitin-specific proteases (USPs) family, impact cancer through diverse mechanisms. Non-coding RNAs (ncRNAs), notably miRNAs, lncRNAs, and circRNAs, add to the complexity of cancer. Recently, the interplay between USPs and ncRNAs has been demonstrated to affect key cancer traits, including proliferation, apoptosis, metastasis, angiogenesis, and stem cell characteristics. The connection between USPs and ncRNAs also extends to control metabolic reprogramming and immune modulation within the TME, comprehensively shaping cancer behaviors. Targeting the USP-ncRNA axis presents a promising avenue for therapeutic intervention, offering potential in overcoming treatment resistance. By further leveraging nanotechnological advancements in precise delivery, this review highlights the translational potential of USP-ncRNA interactions for cancer therapy.